2016
DOI: 10.1073/pnas.1522691113
|View full text |Cite
|
Sign up to set email alerts
|

Antigen clasping by two antigen-binding sites of an exceptionally specific antibody for histone methylation

Abstract: Antibodies have a well-established modular architecture wherein the antigen-binding site residing in the antigen-binding fragment (Fab or Fv) is an autonomous and complete unit for antigen recognition. Here, we describe antibodies departing from this paradigm. We developed recombinant antibodies to trimethylated lysine residues on histone H3, important epigenetic marks and challenging targets for molecular recognition. Quantitative characterization demonstrated their exquisite specificity and high affinity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Another question is whether monoclonal antibodies are a true representation of the antibodies found in clinical samples. The selection of these antibodies may lead to a population of monoclonal antibodies that generally have a lower avidity towards DNA than is found for anti-DNA in sera 31 . Moreover, the constants are calculated using a 1:1 binding model, and it is debatable whether one can use this approximation, because antibodies have two binding sites 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Another question is whether monoclonal antibodies are a true representation of the antibodies found in clinical samples. The selection of these antibodies may lead to a population of monoclonal antibodies that generally have a lower avidity towards DNA than is found for anti-DNA in sera 31 . Moreover, the constants are calculated using a 1:1 binding model, and it is debatable whether one can use this approximation, because antibodies have two binding sites 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the B-cell proliferation and antibodies secretion can be summarized as where r Ab reflects the rate of antibody production, and δ Ab is the natural decaying rate of IgG, which is approximately 28 days 34 . The parameter β Ab = ρβ Ag denotes the removing rate of antibodies from binding with the antigens where ρ > 0 reflect potential varied stoichiometry in the antigen-antibody interaction 36 , 37 . Fitting the model Eqs ( 3 )–( 5 ) to the average IgG data of all subjects resulted in a classic antibody response picture, namely a lag phase follows by an exponential phase before reaching a plateau (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SDS-PAGE showed that Fabs were >90% pure. Fab binding to targets was assessed by a bead binding assay, as described previously (84). Briefly, biotinylated Fabs were immobilized on Dynabeads M280 streptavidin, and then excess biotinbinding sites on streptavidin were blocked with biotin.…”
Section: Expression Purification and Characterization Of Recombinantmentioning
confidence: 99%